CuNi catalyst and preparation method and application thereof

CuNi catalyst was prepared by electrochemical polishing and electrodeposition on nickel foil, which solved the problem that traditional thermally catalyzed HMF hydrogenation reaction required high temperature and high pressure and precious metal catalysts, and achieved efficient conversion of HMF under mild conditions Effect.

CN119465328AActive Publication Date: 2025-02-18NORTHEAST FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411645055.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Traditional thermally catalyzed HMF hydrogenation reaction requires high temperature and high pressure conditions, and hydrogen comes from fossil resources, which reduces the sustainability of the reaction and increases the cost of the use of precious metal catalysts.

Method used

CuNi catalyst was used to deposit copper microsphere particles on nickel foil by electrochemical polishing and electrodeposition methods, and a CuNi bimetallic catalyst was prepared for electrocatalyzing the hydrogenation reaction of HMF.

Benefits of technology

The efficient conversion of HMF under mild conditions was achieved, and the yield and Faraday efficiency of the product 2,5-dihydroxymethylfuran reached 90% and 83.4%, reducing costs and improving the sustainability of the reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465328A_ABST
    Figure CN119465328A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalytic biomass conversion catalysts, and particularly discloses a CuNi catalyst and a preparation method and application thereof.The preparation method comprises the steps that a nickel foil serves as a substrate, and the surface of the nickel foil is pretreated to remove an oxidation film on the surface of the nickel foil; the pretreated nickel foil serves as a working electrode, Ag / AgCl serves as a reference electrode, a 2 * 1 cm platinum sheet serves as a counter electrode, deposition electrolyte is added, stirring is continuously conducted at the rotating speed of 600 rmp, deposition is conducted through CV circulation under the voltage of + 0.5 V to-2 Vvs Ag / AgCl, and the coulombic amount of deposition is 5-20 C; and washing the obtained precipitate with water and ethanol respectively, and then drying in a vacuum drying oven at 60-70 DEG C for 7 minutes to obtain the CuNi bimetallic catalyst. When the CuNi catalyst prepared by the method is used for synthesizing 2, 5-dimethylolfuran through electro-catalysis and hydrogenation of 5-hydroxymethylfurfural, HMF is successfully converted in a mild and clean mode, and the method has the advantages of being low in cost, high in yield, very high in practicability and very good in industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic biomass conversion catalysts, in particular to a CuNi catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of industrial level, the excessive use of fuels such as coal and oil has led to a large reduction in fossil resources and caused irreversible damage to the human body and the environment. Therefore, more and more attention has been paid to green energy - biomass energy. Due to its renewability, biomass energy is called the "sleeping giant". 5-Hydroxymethylfurfural (HMF) is an important biomass platform compound, which can be produced into 2,5-dihydroxymethylfuran (DHMF) by catalytic hydrogenation. DHMF is a biomolecular material with special synthetic properties and has great potential to improve the performance of polyester materials. Therefore, researchers have carried out extensive research in recent years.

[0003] The research on traditional thermal catalytic HMF hydrogenation reaction is relatively mature, but it usually requires high temperature above 100°C and high pressure of 3MPa or even higher to achieve. In addition, the hydrogen involved in the reaction still mainly comes from the extraction of fossil resources, which reduces the sustainability of the entire reduction process. Electroreduction technology provides a milder, more controllable and cleaner strategy for the value-added production of biomass, without involving H2, and therefore has broader application prospects. In the catalytic process, the role of the catalyst is crucial. Traditional thermal catalysis usually uses expensive precious metals such as Ag and Pt for hydrogenation reactions, which further increases the cost. Therefore, the development of non-precious metal catalysts to catalyze the hydrogenation of 5-hydroxymethylfurfural has good practicality. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a CuNi catalyst and a preparation method and application thereof.

[0005] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0006] One of the objects of the present invention is to provide a method for preparing a CuNi catalyst, comprising the following steps:

[0007] S1. Pretreatment of substrate: using nickel foil as substrate, pretreatment is performed on the surface of the nickel foil to remove the oxide film on the surface of the nickel foil;

[0008] S2. Electrodeposition: The pretreated nickel foil was used as the working electrode, Ag / AgCl as the reference electrode, and a 2×1 cm platinum sheet as the counter electrode. The deposition electrolyte was added and stirred at a continuous speed of 600 rpm. The deposition was performed using a CV cycle at a voltage of +0.5 V to -2 V vs Ag / AgCl, and the coulomb amount of the deposition was 5-20C. The obtained precipitate was rinsed once with water and once with ethanol, respectively, and then dried in a vacuum drying oven at 60-70°C for 7 min to obtain a CuNi bimetallic catalyst.

[0009] Furthermore, the step S1 specifically includes:

[0010] S11. Cut the nickel foil (Ni≥99.99%) into a size of 2 cm×1 cm and rinse it repeatedly with ethanol and ultrapure water for 3 times;

[0011] S12. Connect the cathode of the dual-electrode DC power supply to the graphite rod electrode, and the anode to the treated nickel foil. Place them in an electrochemical polishing solution for electrochemical polishing. Keep the solution stirring at a speed of 400 rpm, apply a constant voltage of 7 V for electrolysis. After 2 min 30 s, the polishing is completed, and the anode nickel foil becomes bright. After removing the nickel foil, rinse it twice with ethanol and water respectively, and the oxide film on the surface of the nickel foil is completely removed.

[0012] Furthermore, the preparation method of the electrochemical polishing solution is:

[0013] 30 ml of 99% pure ethanol and 10 ml of perchloric acid were mixed in an ice water bath, and then ultrasonically mixed for 30 seconds to obtain an electrochemical polishing solution.

[0014] Furthermore, in step S2, the deposition electrolyte is prepared by:

[0015] Weigh 0.8g Cu(NO 3 ) 2 6H 2 O and 272 mg of sodium dodecyl sulfate were placed in a three-electrode single-chamber electrolytic cell filled with 40 ml of ultrapure water, at which the copper ion concentration was 0.0677 mol / L; the above solution was mixed evenly by ultrasonic treatment for 20 minutes, and then transferred to a water bath with a constant temperature of 65°C for 15 minutes. After the water bath, deposition was quickly carried out to obtain a deposition electrolyte.

[0016] Furthermore, in step S2, the scanning rate of CV is 100 mV / s.

[0017] The second object of the present invention is to provide a CuNi catalyst prepared by the above method.

[0018] The third object of the present invention is to provide a CuNi catalyst for use in the electrocatalytic hydrogenation of 5-hydroxymethylfurfural to synthesize 2,5-dihydroxymethylfuran.

[0019] The mechanism of the present invention is as follows: the present invention electrochemically polishes the Ni foil in a strong acid solution, then electro-deposits the copper microsphere particles to be quantitatively deposited on the Ni foil, and then dries to obtain the CuNi non-precious metal material. The Cu in the CuNi catalyst has excellent ability to adsorb the reaction substrate HMF, and Ni can provide an appropriate amount of adsorbed hydrogen without causing a large amount of H 2 The production of.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) Compared with the traditional solid phase reaction method and solvent thermal method, the method for preparing CuNi catalyst of the present invention has the advantages of simple synthesis, low price, low synthesis temperature, high material reproducibility and stable material structure.

[0022] (2) The present invention rationally controls the amount of Cu deposited on the Ni sheet surface, regulates the number of active sites on the Cu-Ni interface, and enhances the interaction between the CuNi catalyst and HMF, which can effectively solve the problems of poor catalytic effect, low product conversion rate and low selectivity during the electrocatalytic reduction of 5-hydroxymethylfurfural.

[0023] (3) The CuNi catalyst prepared by the present invention successfully converts HMF in a mild and clean manner when electrocatalyzing 5-hydroxymethylfurfural hydrogenation to 2,5-dihydroxymethylfuran, and has the advantages of low cost, high yield, high practicality and good industrialization prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention provides a process flow chart for preparing the CuNi catalyst.

[0025] Figure 2 This is the SEM image of the CuNi catalyst prepared in Example 1.

[0026] Figure 3 This is the XRD pattern of the CuNi catalyst prepared in Example 1.

[0027] Figure 4 DHMF production efficiency of 10C material at different potentials.

[0028] Figure 5 DHMF Faraday efficiency of three materials at different potentials.

[0029] Figure 6 The Faradaic efficiency and conversion rate of the catalytic reaction of 10C material at different HMF concentrations.

[0030] Figure 7 Conversion rate and DHMF Faradaic efficiency of 10C material in 8 cycles. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0032] Unless otherwise specified, the raw materials, reagents and equipment used in the following examples were commercially available.

[0033] Example 1

[0034] Reference Figure 1 , take three pieces of Ni foil of 2×1cm, rinse them in ethanol and ultrapure water in turn, then place them in a mixed solution of 30ml ethanol (purity 99%) and 10ml perchloric acid (analytical grade) and electrochemically polish them at a voltage of 7V through a DC power supply. After 2min30s, the electrolysis is terminated, and the nickel foil is removed and rinsed twice with ethanol and water respectively. Then 0.8g Cu(NO 3 ) 2 6H 2 O and 272mg sodium dodecyl sulfate were placed in a three-electrode single-chamber electrolytic cell filled with 40ml ultrapure water for 20 minutes of ultrasonic mixing, and then transferred to a water bath at a temperature of 65°C for 15 minutes. After the water bath, deposition was carried out quickly. The treated nickel foil was used as the working electrode, Ag / AgCl was used as the reference electrode, and a 2×1cm platinum sheet was used as the counter electrode. The mixed solution was used as the deposition electrolyte, and the speed was continuously stirred at 600rmp. The CuNi bimetallic catalyst was deposited by CV cycle at a voltage of +0.5V~-2Vvs Ag / AgCl, where the CV scan rate was 100mV / s. The coulomb amounts deposited on three identical nickel foils were 5C, 10C, and 20C, respectively. The obtained materials were rinsed with water and ethanol once, and then dried in a vacuum drying oven at 60-70°C for 7 minutes to obtain the final CuNi catalyst with different deposition amounts.

[0035] The three CuNi catalysts with deposition amounts of 5C, 10C, and 20C obtained in this example were analyzed by scanning electron microscopy. Figure 2 As shown by Figure 2 It can be seen that the distribution of copper particles on the Ni foil is nearly circular island particles. Different deposition amounts lead to different distribution states of Cu particles. The copper particles of the 5C material are evenly distributed on the Ni foil but the number of copper particles is small. The number of copper particles in the 10C material is large and evenly distributed on the substrate. The 20C material is clustered due to the excessive number of copper particles.

[0036] And by Figure 2 As can be seen in Figure 2, island-shaped Cu particles successfully grew on the Ni surface. These morphological characterizations indicate that different deposition amounts are an effective strategy to control the number of active sites in CuNi catalysts.

[0037] The CuNi catalyst prepared in this example was subjected to X-ray diffraction (XRD) analysis, and the results are as follows: Figure 3 As shown by Figure 3 It can be seen that the characteristic peaks of Cu appear at 43.3°, 50.4° and 74.1°, and the characteristic peaks of substrate Ni appear at 44.5°, 51.8° and 76.4°, which indicates that the Cu particles are successfully deposited on the nickel sheet and different deposition amounts lead to consistent valence states of the deposited metal.

[0038] Example 2

[0039] The 5C, 10C and 20C materials prepared in Example 1 were used as working electrodes in the H cell for electrocatalytic reduction of HMF to generate DHMF. The cathode and anode of the H cell were separated by a proton membrane (model: DuPont Nafion 117), and the cathode electrolyte was H containing 20 mM / L HMF. 3 BO 3 -KOH solution, the anolyte is H 3 BO 3 -KOH solution (H in electrolyte) 3 BO 3 The concentration is 0.5 mol / L, KOH is added to adjust the pH to 9.2); a Pt sheet electrode is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and the CuNi material described in the present invention is used as a working electrode. When electrolyzing HMF, five potentials are selected within the potential range of -0.36 to -0.56 Vvs RHE for constant potential polarization. During the reaction, the solution in the cathode chamber changes from light yellow to colorless, indicating the gradual consumption of HMF. The present invention quantifies HMF and DHMF before and after the reaction by Agilent high performance liquid chromatography. The production efficiency and Faraday efficiency of the product DHMF are calculated using the following formulas:

[0040] DHMF yield = (actual yield / theoretical yield) × 100%;

[0041] The Faradaic efficiency (FE) of DHMF = the molar amount of DHMF produced × the number of electrons transferred × 96485 / the amount of charge actually passed through the reaction.

[0042] The results are as follows Figure 4 and Figure 5 As shown by Figure 4 and Figure 5It can be seen that with the continuous increase of reaction potential, the Faradaic efficiency of DHMF under the action of 5C, 10C and 20C materials shows a trend of first increasing and then decreasing with the increase of potential. In particular, the performance of 10C catalyst has been higher than that of 5C and 20C materials at different potentials. At a potential of -0.46 V vs RHE, the Faradaic efficiency of DHMF under the action of 10C catalyst reaches 83.4%, the yield of DHMF is as high as 90%, and the conversion rate of DHMF at different potentials continues to increase with the increase of potential, indicating that the catalyst has a good catalytic effect.

[0043] Example 3

[0044] The 10C material prepared in Example 1 was used as a working electrode in an H cell for electrocatalytic reduction of HMF to generate the product DHMF. At this time, the content of HMF in the cathode electrolyte was controlled, and the HMF content was increased from 20mM to 100mM, and the anode electrolyte was still a H3BO3-KOH solution; the Pt sheet electrode was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. When electrolyzing HMF, constant potential polarization was performed at a potential of -0.61Vvs RHE, and the Faraday efficiency and conversion rate of the product were calculated, wherein the amount of hydrogen produced was detected by high-performance gas chromatography. The results are shown in FIG. Figure 6 As shown by Figure 6 It can be seen that at a concentration of 100 mM HMF, the Faradaic efficiency of DHMF is close to 80%, indicating that the 10C catalyst is expected to help actual industrial production and expand its scale.

[0045] Example 4

[0046] The 10C material prepared in Example 1 was used as a working electrode in an H cell for electrocatalytic reduction of HMF to generate the product DHMF. The cathode and anode electrolytes were still H3BO3-KOH solutions; the Pt sheet electrode was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. Constant potential polarization was performed at the optimal reaction potential of -0.46V vs RHE. After one reaction, a new electrolyte was immediately replaced, and an equal amount of HMF was added. The 10C material was recycled for multiple times to test the stability of the material. After each cycle, the electrolyte in the cathode chamber was taken to test the reactant and product contents, and the conversion rate of each cycle and the Faraday efficiency of DHMF were calculated. The results are shown in Figure 2. Figure 7 As shown by Figure 7 It can be seen that the 10C material has good cycle stability and can still maintain more than 70% of the Faraday efficiency after 8 cycles, while the conversion rate changes by no more than 10%.

[0047] In summary, the CuNi catalyst prepared in the present invention exhibits excellent catalytic performance when applied to the electrocatalytic HMF reduction reaction. At a reaction potential of -0.46 V vs RHE, the product DHMF yield and Faraday efficiency reach 90% and 83.4%, respectively.

[0048] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a CuNi catalyst, characterized in that: The following steps are involved: S1. Pretreatment of substrate: using nickel foil as substrate, pretreatment is performed on the surface of the nickel foil to remove the oxide film on the surface of the nickel foil; S2. Electrodeposition: The pretreated nickel foil was used as the working electrode, Ag / AgCl as the reference electrode, and a 2×1 cm platinum sheet as the counter electrode. The deposition electrolyte was added and stirred at a continuous speed of 600 rpm. The deposition was performed using a CV cycle at a voltage of +0.5 V to -2 V vs Ag / AgCl, and the coulomb amount of the deposition was 5-20C. The obtained precipitate was rinsed once with water and once with ethanol, respectively, and then dried in a vacuum drying oven at 60-70°C for 7 min to obtain a CuNi bimetallic catalyst.

2. The method for preparing a CuNi catalyst according to claim 1, characterized in that: The step S1 specifically includes: S11. Cut the nickel foil (Ni≥99.99%) into a size of 2 cm×1 cm and rinse it repeatedly with ethanol and ultrapure water for 3 times; S12. Connect the cathode of the dual-electrode DC power supply to the graphite rod electrode, and the anode to the treated nickel foil. Place them in an electrochemical polishing solution for electrochemical polishing. Keep the solution stirring at a speed of 400 rpm, apply a constant voltage of 7 V for electrolysis. After 2 min 30 s, the polishing is completed, and the anode nickel foil becomes bright. After removing the nickel foil, rinse it twice with ethanol and water respectively, and the oxide film on the surface of the nickel foil is completely removed.

3. The method for preparing the CuNi catalyst according to claim 2, characterized in that: The preparation method of the electrochemical polishing liquid is: 30 ml of 99% pure ethanol and 10 ml of perchloric acid were mixed in an ice water bath, and then ultrasonically mixed for 30 seconds to obtain an electrochemical polishing solution.

4. The method for preparing the CuNi catalyst according to claim 1, characterized in that: In the step S2, the deposition electrolyte is prepared by: 0.8 g Cu(NO3)2·6H2O and 272 mg sodium dodecyl sulfate were weighed separately and placed in a three-electrode single-chamber electrolytic cell filled with 40 ml ultrapure water. At this time, the copper ion concentration was 0.0677 mol / L. The above solution was mixed evenly by ultrasonic for 20 minutes, and then transferred to a water bath at a temperature of 65°C for 15 minutes. After the water bath, deposition was quickly carried out to obtain a deposition electrolyte.

5. The method for preparing the CuNi catalyst according to claim 1, characterized in that: In step S2, the scanning rate of CV is 100 mV / s.

6. A CuNi catalyst prepared by the method according to any one of claims 1 to 5.

7. Use of the CuNi catalyst as claimed in claim 6 in electrocatalytic hydrogenation of 5-hydroxymethylfurfural to synthesize 2,5-dihydroxymethylfuran.

Citation Information

Patent Citations

  • Preparation method and application of nickel-copper bimetallic nanotube catalyst material

    CN114622237A

  • Surface-oxidized nickel-copper alloy catalyst and preparation and application thereof

    CN118086958A